THE ROLE OF BUKHARA AND OTHER CITIES IN THE MILITARY ART AND ARMY STRUCTURE OF KHOREZMSHAHS - Muyiddinov Bekali (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: this article will scientifically analyze how the Military Art of the Khorezmshah state is organized, the general structure and development of the army, the emergence of military centers of the rise, and the high and incomparable place in it of the cities that are part of Khorezm, especially the presence of centers such as the city of Bukhara and what the main weapons of the.